ANALISIS KONSTRAIN DAN SUSTAINABILITAS PENGEMBANGAN PERTANIAN DATARAN TINGGI PEGUNUNGAN ARFAK DI PAPUA BARAT - Meky Sagrim; Agus I. Sumule; Deny A. Iyai; Michael Baransano (Caraka Tani: Journal of Sustainable Agriculture, 2016)
The variability and complexities of limiting factors in development have been exist in community. Works in agriculture sector need lot of attention in development plan. Therefore, it needs a concise study of constraints and future agriculture development. A descriptive study and FGD technique and snowball sampling method were used to approach local community in gaining related information. The findings reported that the primary constraints hampered local communities were farmers’ motivation, state officers’ performances, and capital investment performances. The available quality seeds and breeds will have strategic position in planned agriculture development.